PENGARUH PEMBERIAN BATANG POHON PEPAYA (Carica Papaya) SEBAGAI PAKAN KASAR TERHADAP PRODUKSI SUSU SAPI FH DI BOYOLALI: THE EFFECT OF FEEDING CARICA PAPAYA STEM AS CRUDE FEED ON MILK PRODUCTION OF FH DAIRY CATTLE IN BOYOLALI - Purwadi, Purwadi; Kurniansyah, Dwi (Tropical Animal Science, 2023)
The Aims of reasrch are to know the Effect of Feeding Carica Papaya Stem as Crude Feed On Milk Production of Friesian Holstein Dairy Cow’s In Boyolali. This study was conducted in July 2018 using 16 FH cattle with an average body weight of 431.75+ 50.99 kg (CV = 11.82%) and average milk production per day of 11.12+ 0.96 liters (CV = 8.61%). Cows Housing in a station barn sytem. Average Production period of cattle is the 2nd lactation period, and 2 - 5 month of lactation. This is study using a completely randomized design with four treatments and four replicationt, T0 : 30% brand pollard, 10% tofu waste, 60% elephant grass, T1 : 30% brand-pollard, 10% tofu waste, 40% elephant grass (Pennisetum Purpureum), 20% papaya stem, T2 : 30% brand-pollard, 10% tofu waste, 20% elephant grass, 40% papaya stem, T3 : 30% brand-pollard, 10% tofu waste, 0% elephant grass, 60% papaya stem. The parameters examined were feed consumption and milk production for a month. The results of this study were: Dry matter consumption between T0 with T1,T2 and T3 were significant (P<0,05), whereas the treatment between T1,T2 and T3 are unsignificant (P>0,05). Crude protein consumption was difer (P <0.01) between T1, T2 with T0 and T3, everthough for the treatment between T3 and T0 were significant (P <0.01). TDN consumption between T0, T1, T2 and T3 were unsignificant (P> 0.05). The average production of milk in treatments T0, T1, T2 and T3 was unsignificant (P> 0.05). The conclusion of this study is the use of carica papaya stem as a rough feed substitute for fresh forage can maintain the milk productivity of Friesian Holstein dairy cow's. The provision of 40% carica papaya srem combined with 20% elephant grass as crudefeed results milk production as well as feeding 60% elephant grass. Keywords: FH dairy cow, Carica Papaya Stems, Feed Consumption, Milk Production